Nanoscale engineered exosomes for dual delivery of Sirtuin3 and insulin to ignite mitochondrial recovery in myocardial ischemia-reperfusion - Jiaxin Yang; Xinyi Yun; Weihan Zheng; Huihui Zhang; Zi Yan; Youyu Chen; Wanting Xue; Siqi Mi; Ziyue Li; Hanxiao Sun; Guozhi Xiao; Zhenning Dai; et al. (Journal of Nanobiotechnology)
Abstract Background Acute myocardial infarction remains a leading cause of mortality, with ischemia-reperfusion (I/R) injury causing severe myocardial damage through mitochondrial dysfunction. While mesenchymal stem cell-derived exosomes (MSC-Exo) show therapeutic potential, their limited targeting and insufficient mitochondrial protection restrict clinical application. Results We developed a novel engineered exosome platform (Exo-I-S) using an IRES-driven bicistronic plasmid to co-load Sirtuin3 (SIRT3) and GPI-Insulin, aiming to enhance targeting efficiency and mitochondrial protection. The platform was evaluated in both in vitro and in vivo models of myocardial I/R injury. In vitro, Exo-I-S achieved faster cellular uptake, improved mitochondrial function, and reduced oxidative stress in H9c2 cells. The platform activated PI3K/AKT signaling, enhanced Glut4 translocation, and improved mitochondrial respiratory capacity. In a rat I/R injury model, Exo-I-S significantly reduced infarction size, improved cardiac function, and enhanced glucose metabolism, with superior therapeutic outcomes compared to unmodified exosomes. Conclusions The dual functionality of Exo-I-S, combining insulin-mediated targeting with SIRT3-driven mitochondrial protection, provides a promising strategy for I/R injury treatment. Future studies should focus on optimizing targeting specificity and developing sustained release mechanisms to enhance clinical applicability.